Effect of thermal treatment on the crystal structure and morphology of zirconia nanopowders produced by three different routes - MM Rashad, HM Baioumy, . (2008)
Zirconia ZrO2 nanopowders have been successfully prepared via three processing routes, namely, conventional precipitation (CP), citrate gel combustion (CGC) and microemulsion refined precipitation (MRP). The formed zirconia particles were characterized using X-ray diffraction analysis (XRD), scanning electron microscope (SEM), Fourier transformer infrared (FT-IR) spectroscopy and UV–visible absorption spectrum. The results showed that the CP route led to the formation of tetragonal ZrO2 phase with low crystallinity at 700 °C and the formed tetragonal phase was transformed to monoclinic ZrO2 phase at temperatures ranged from 1000 to 1200 °C.